Utilization of Lake Toba culinary identity for gastronomic tourism development - Cecep Ucu Rakhman; Arini Shofi Elmia; Sondjana Ali Suganda; Ahmad Esa Abdul Rahman (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This research explores the potential of gastronomic tourism in the Lake Toba region of Indonesia, focusing on the unique culinary identity and traditions of the Batak tribe. Batak culinary practices are firmly rooted in local traditions and environmental conditions, with major traditional foods and drinks such as Tuak, Na Niura, and Mie Gomak having strong cultural values. Currently, Lake Toba gastronomic tourism has not become a leading tourism destination. The purpose of this study is to examine how environmental and cultural factors affect local cuisine and beverages in the Lake Toba region and to identify challenges and opportunities in promoting these gastronomic assets effectively. This qualitative research uses interviews, observations, and documentation to collect data. Key stakeholders, including local business owners and Batak cultural experts were interviewed using non-probability snowball sampling to gain comprehensive insights into the region's culinary identity. The results of the study highlight the cultural significance and potential tourist attraction of traditional Batak food and beverages. However, challenges such as tourists' lack of knowledge about local cuisine were identified. The study shows that a more structured and strategic approach, including annual food festivals and culinary tours, is needed to increase the demand for Lake Toba's Gatronomi tourism. This study underscores the need for an annual Lake Toba Gastronomy festival to utilize local culinary heritage, thereby increasing cultural preservation and tourism development in the Lake Toba region.